Analysing Middle Grades1 Science Textbooks for their Potential to Promote Scientific Inquiry - Bansal, Garima (JOURNAL OF INDIAN EDUCATION, 2014)
Textbooks constitute the toolkit (Chinn et. al., 2002) used by teachers to foster scientific temper among their students. By this token, this study seeks to examine the middle school science textbooks of two publications, NCERT and Eklavya, for the ways in which they support scientific inquiry. The 5E model of inquiry based science learning is used to analyse textbook activities for their ability to support inquiry. A proposed plan in terms of centrally placing inquiry based tasks in curriculum organisation, furthering student engagement, and facilitative role of teachers is presented. It is hoped that contextualising science by the means of inquiry based textbooks would strengthen the bonds between science and society and develop critically inquiring minds contributing to the progress of scientific pursuit throughout their lives.